Pelatihan Kewirausahaan dalam Upaya Meningkatkan Kesejahteraan Masyarakat di Desa Simaninggir Kecamatan Sitahuis Kabupaten Tapanuli Tengah - Maeka Rosianna Tarihoran; Masnia Silitonga (Trending: Jurnal Manajemen dan Ekonomi, 2024)
Entrepreneurship training in Simaninggir village has the main objective of empowering the community to be able to create independent economic welfare. Through this training, it is hoped that the Simaninggir village community can explore their potential and local resources to create new business opportunities. That way, they do not only depend on the agricultural sector, but also have additional sources of income. In addition, entrepreneurship training also aims to improve the quality of life of the Simaninggir village community as a whole. By having their own business, the Simaninggir village community can increase family income, create jobs, and contribute to the development of Simaninggir village.